QCD Phase Diagram in a Nonlocal SU(3) NJL Model with Lattice-Inspired Form Factors - Izzo Villafañe, María Florencia (2017)
We study the QCD phase diagram in the framework of a nonlocal three-flavor quark model. We determine the model parameters from vacuum meson phenomenology, considering lattice QCD-inspired nonlocal form factors. Then we analyze the features of the deconfinement and chiral restoration transitions for systems at nonzero temperature and chemical potential.